Young Adult Lifestyle and Cardiovascular Risk (Global Journal of Human-Social Science, 2025)
Introduction Lifestyle directly influences cardiovascular health therefore encouraging young people to adopt healthy habits through physical activity dietary re-education and non-use of tobacco can prevent the emergence of these diseases Objectives To evaluate the factors that predispose the cardiovascular health of young adults to risks making a correlation with lifestyle Methods This is a cross-sectional study with a quantitative approach Some data were collected such as blood pressure muscle strength total and fractionated cholesterol blood glucose anthropometric measurements bioimpedance heart rate double product recovery after exercise test and lifestyle Results There were 52 participants and only 31 completed all assessments The mean age was 42 5 6 1 years The majority were female there were six hypertensive patients two with isolated systolic hypertension and four had high blood glucose all recovered their heart rate and the double product at the end of the fifth minute after exercise The cardiovascular risk measured by the Framingham score was moderate at 12 and severe for 9 of participants the rest were classified as low risk The Framingham score was associated with lifestyle r-043 Cardiovascular risk was significantly increased for those participants who declared living in a stressful environment p 0 03 for smokers p 0 003 for males p 0 0006 for sedentary people p 0 003 Conclusion Severe and moderate cardiovascular risk was found for 22 of the sample Male sex smoking sedentary lifestyle and living in a stressful environment were the main cardiovascular risk factors found
Keywords: cardiovascular risk; chronic diseases; lifestyle